Human RECQ1 interacts with Ku70/80 and modulates DNA end-joining of double-strand breaks. - Swetha Parvathaneni; Alexei Stortchevoi; Joshua A Sommers; Robert M Brosh; Sudha Sharma (PLoS ONE, 2013)
Genomic instability is a known precursor to cancer and aging. The RecQ helicases are a highly conserved family of DNA-unwinding enzymes that play key roles in maintaining genome stability in all living organisms. Human RecQ homologs include RECQ1, BLM, WRN, RECQ4, and RECQ5β, three of which have been linked to diseases with elevated risk of cancer and growth defects (Bloom Syndrome and Rothmund-Thomson Syndrome) or premature aging (Werner Syndrome). RECQ1, the first RecQ helicase discovered and the most abundant in human cells, is the least well understood of the five human RecQ homologs. We have previously described that knockout of RECQ1 in mice or knockdown of its expression in human cells results in elevated frequency of spontaneous sister chromatid exchanges, chromosomal instability, increased load of DNA damage and heightened sensitivity to ionizing radiation. We have now obtained evidence implicating RECQ1 in the nonhomologous end-joining pathway of DNA double-strand break repair. We show that RECQ1 interacts directly with the Ku70/80 subunit of the DNA-PK complex, and depletion of RECQ1 results in reduced end-joining in cell free extracts. In vitro, RECQ1 binds and unwinds the Ku70/80-bound partial duplex DNA substrate efficiently. Linear DNA is co-bound by RECQ1 and Ku70/80, and DNA binding by Ku70/80 is modulated by RECQ1. Collectively, these results provide the first evidence for an interaction of RECQ1 with Ku70/80 and a role of the human RecQ helicase in double-strand break repair through nonhomologous end-joining.